VARIASI TEMPERATUR TERHADAP PERUBAHAN NILAI KEKUATAN SEAL PADA MATERIAL KEMASAN LENTUR MULTI LAYER PET-ALU FOIL-LDPE - Emmidia Djonaedi; Diyah Ayu; Dini Handayani (Jurnal Poli-Teknologi, 2019)
Plastic is common flexible material for packaging. One of common combination multilayer material are PET-ALU FOIL-LDPE. Multiplayer packaging through some step. Last steps is bag making. Bag making was processed with sealing inner plastic material in certain position with heat. Transverse direction (TD) for horizontal seal and Machine Direction (MD) for horizontal seal. The aim to gain a good seal strength is to avoid broken while filling process. Some factors that affect seal strength are temperature, time and pressure of sealing process. This research focus on seal strength value while temperature changed. Temperature starts from 140C to 240C with interval 20C. This experiment gained two optimum temperature and seal strength for TD and MD. Seal strength TD is 31 N/mm at 180C and seal strength 34 N/15mm at 160C for MD.